Recovery kinetics and ordering in irradiated bulk metallic glasses - Petrusenko, Y.; Bakai, A.; Neklyudov, I.; Borysenko, V.; Barankov, D.; Astakhov, O.; Macht, M.P. (Вопросы атомной науки и техники, 2008)
Accumulation and recovery kinetics of radiation damages in Zr₄₆.₈Ti₈.₂Cu₇.₅Ni₁₀Be₂₇.₅ and Zr₅₂.₅Ti₅Cu₁₇.₉Ni₁₄.₆Al₁₀ metallic glasses was investigated by means of low temperature electron irradiation and electrical resistance measurements. The linear dose dependence of resistance is a manifestation of accumulation of irradiation defects without considerable interaction between them. The recovery spectrum of irradiation-induced electrical resistance was obtained for the 85…300 K temperature range. Two annealing peaks located at T~150 K and ~225 K were resolved. The present data suggest the conclusions that the defect mobility is a thermally activated process, and that the activation energy is not as high as that for vacancies in crystalline alloys. These results are in agreement with the polycluster model of metallic glass structure.